FRAGMENTATION OF INTERNATIONAL LAW PARADIGM AND CONFLICT OF JURISDICTIONS OF INTERNATIONAL COURTS WITH SPECIAL REFERENCE TO THE EUROPEAN COURT OF JUSTICE - Đajić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Fragmentation of international law can be studied from a variety of perspectives and the one chosen for this research is whether and how the conflict of jurisdictions (or other types of conflicts, in terms of interpretation or enforcement) of international judicial and quasi-judicial bodies affect the unity of international law. While the answer might seem to be too obvious to justify the question, it is still not to be too easily assumed. The second issue discussed in this paper is whether and to what extent the external authority of an international court affects the resolution of a conflict. Both issues are too grand for a single paper so the research will be focused solely on three case studies involving the European Court of Justice: Mox Plant, Kadi and Achmea cases. In all three of them the EU Court of Justice clashed with another adjudicative authority and prevailed in the first two but seems to have lost a battle in the third. The article explores the reasons for these outcomes relying inter alia on the concept of external authority of a judicial institution. These findings are coupled with discussion on how these outcomes can be assessed from the perspective of (de)fragmentation of international law.